Meeting the challenges of teaching in a different cultural environment – evidence from graduate management schools in Thailand. (15th January 2016) - Kainzbauer, Astrid; Hunt, Brian
Abstract : In this paper we describe the efforts of foreign university teachers in graduate schools in Thailand as they incorporate cultural knowledge into their classroom teaching styles and methodology. Through in-depth semi-structured interviews we have gathered qualitative data on the teachers' concerns, mindsets and their proposed solutions. We build up our discussion in several stages. We set the scene by discussing the importance of cultural sensitivity in settings where teacher and learners have different cultural backgrounds. We then introduce the concept of cultural intelligence and use this to help us examine the literature on cultural sensitivity in teaching from a new perspective. We then describe the cultural context of teaching in Thailand and offer empirical data from our respondents' experiences. From our research data we identified five main aspects of Thai culture where teachers felt the need to expand/adapt their existing teaching repertoires. These aspects are: fun/ sanuk ; hierarchy/ kreng jai ; authority with a kind heart/ jai dee ; collectivist group activities; and localized class content. We discuss our findings in relation to cultural adjustments that the teachers sought to make and, in conclusion, link this discussion to our earlier examination of cultural intelligence.